INFLUENCE OF CRISIS COMMUNICATION ON THE RELATIONSHIP BETWEEN BRAND IDENTITY AND EMPLOYEE BRAND SUPPORT IN AVIATION INDUSTRY: A BIBLIOMETRIC REVIEW AND NEW RESEARCH PATHS - Shafiq Ayub; Rosmiza Bidin; Mohd Nizam Osman; Jen Sern Tham (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2025)
In the aviation industry, this research presents a bibliometric analysis of the existing literature investigating the impact of crisis communication on the association between brand identity and employee brand support. Due to the sensitive nature of the aviation industry, it is necessary to have a comprehensive understanding of the interplay that exists between crisis communication, brand identity, and employee brand support. This is necessitated by the fact that the aviation industry faces distinct challenges. This review aims to provide a comprehensive analysis of the existing body of literature, identify areas in which additional research is required, and suggest potential avenues for future research.